NATIONAL CULTURE IN THE CONDITIONS OF PLEBEIZATION - Davydiuk, V. F. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the progress trends of culture are considered in town and mud flow. It is accented on plebeizatsii cultures and its features. The features of the poboutouvannya Ukrainian folk culture are certain in ХХІ age. The question of etnomodernou is considered.